Revitalizing Face-to-Face Local Gaming Experience through Mobile Mini Games - Yediya Juan; Teuku Aulia Geumpana; Jude J.L. Martinez (Journal of Games, Game Art, and Gamification, 2016)
with the increase of mobile device usage around the globe, face-to-face communication has degraded and complete prohibition is not realistic. The degradation is not to be prevented as it happens as a side effect of technology. However, balancing usage of mobile device and quality of face-to-face communication is possible. Thus, by approaching users through developing a party genre mobile game, which is not famous as a mobile game at the time, with local multiplayer focus and introducing the given game to users, it is expected that face-to-face communication can be encouraged, thus resulting in mobile party game to become a media for the encouragement. Sample mini game that is a part of party game is developed with the help of Unity game engine as a testing object in which user response is collected. As application testing take place, and target user response is collected, face-toface encouragement is proven and user response is positive towards the game. Sample game testing has effectively reintroduced the existence of nowadays rare party game in mobile platform along with encouraging face-to-face communication, shown by the enthusiasm and enjoyment that audience testers have experienced. In the end, with mobile party game can help by being a media to encourage face-to-face communication and prevent degradation of such communication, future developments of a complete party game in mobile platform is highly encouraged as overall face-to-face communication quality enhancement may be required in the future in order to mitigate degradation.